2022
DOI: 10.33448/rsd-v11i9.31712
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da relação entre a doença do refluxo gastroesofágico, tabagismo e desgastes dentais: revisão narrativa da literatura

Abstract: O objetivo deste estudo foi avaliar a relação entre a doença do refluxo gastroesofágico (DRGE), tabagismo e desgastes dentais. Uma revisão narrativa foi conduzida, realizando-se uma busca eletrônica na literatura, através da plataforma PubMed/Medline. Foram incluídos estudos transversais, de coorte e caso-controle realizados em adultos, abordando, pelo menos, dois dos três temas foco da pesquisa. Estudos em animais, relatos de caso, revisões da literatura, capítulos de livros, cartas, comentários, editoriais e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Nicotine contributes to the development of Gastroesophageal Reflux Disease (GERD), by reducing the pressure of the lower esophageal sphincter, (favoring the return of gastric juice), alteration of salivary secretion levels and by causing chronic coughing (increases the frequency of reflux episodes and prolongs the presence of acidic content in the esophagus) (de Castro Vieira, et al, 2022). Studies have previously shown severe esophagitis due to the use of EC with nicotine (Pasricha & Kochar, 2021).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Nicotine contributes to the development of Gastroesophageal Reflux Disease (GERD), by reducing the pressure of the lower esophageal sphincter, (favoring the return of gastric juice), alteration of salivary secretion levels and by causing chronic coughing (increases the frequency of reflux episodes and prolongs the presence of acidic content in the esophagus) (de Castro Vieira, et al, 2022). Studies have previously shown severe esophagitis due to the use of EC with nicotine (Pasricha & Kochar, 2021).…”
Section: Discussion and Resultsmentioning
confidence: 99%